Polimorfismos do gene TP53 no linfoma de Hodgkin - Viana, Daniel de Araújo (2007)
Hodgkin lymphoma is a hematololgic B neoplasm occurring at patients within any age, however more likely to affect those from 15 to 40 years-old. The TP53 gene is 20kb length gene with 11 exons that encodes the p53 protein, which main function is related to the conservation and integrity of the genetic code. Most cancers show point mutations in the TP53 sequence. The analysis of these mutations allows a better understanding of the function of the diverse domains of the protein and its relationship to tumor suppression. There is only a few data about TP53 polymorphisms and Hodgkin lymphoma. In this manner, in our study we try to detect polymorphisms within the codons 272, 273, 278, 282, 306 of the exon 8 of the TP53 gene in Hodgkin lymphoma. In our survey we analyzed 42 paraffin-embedded tissues from 2000 to 2006. These samples were prepared for DNA extraction and PCR isolation and amplification of the 137bp fragment of the exon 8 of the TP53 gene, using exclusive primers specially designed to our experiment: PFw8 e PRv8. After PCR amplification, the products of the reaction were purified to the Sequencing reaction. The last part of the experiment encoded the bioinformatics analysis of sequences. DNA extraction and PCR amplification were successfully obtained in our study in all the samples. However, the DNA sequencing was only obtained in 32 samples, but there was no characteristic electropherogram of the analyzed region of the gene. Therefore, it was not possible to determine the presence or absence of SNPs in the TP53 exon 8.